Enteric fever in the Pacific: a regional retrospective study from Auckland, New Zealand. Issue 2 (February 2015) - Lane, R. J.; Holland, D.; McBride, S.; Perera, S.; Zeng, I.; Wilson, M.; Read, K.; Jelleyman, T.; Ingram, R. J. H.
Abstract Background There are limited clinical data on enteric fever in the Pacific and New Zealand (NZ) compared with the Indian subcontinent (ISC) and South‐East Asia (SEA). Our objective was to describe enteric fever in Auckland – a large Pacific city, focusing on disease acquired in these regions. Methods We reviewed enteric fever cases hospitalised in Auckland from January 2005 to December 2010. Results Microbiologically confirmed EF was identified in 162 patients. Travel regions: Pacific, 40 cases (25%) (Samoa, 38; Fiji, two), ISC, 72 (44%), SEA, seven (4%), other, three (2%), no travel, 40 (25%). Enteric fever rates for Auckland resident travellers were: India 50.3/100 000; Samoa 19.7/100 000.All Pacific cases were Salmonella Typhi. Of local isolates (without travel history), 38 were S. Typhi (36 fully susceptible, one multi‐drug resistant (MDR) + nalidixic acid resistant (NAR), one unknown) and two S. Paratyphi (both NAR). Of non‐Pacific travel, 56/82 (69%) isolates were S. Typhi, the remainder S. Paratyphi (15 isolates were fully susceptible, only 1% were MDR). Significant associations of serotype and antibiotic resistance with different travel regions and similarity of phage types (local and Pacific) were observed. Headache, vomiting and acute kidney injuries were more frequent with Pacific travel, while abdominal distension and cholecystitis with local disease. Shorter duration of treatment in the Pacific group was seen despite length of stay in hospital not being reduced. Local cases were associated with longer hospital admissions. Conclusions One half of cases in Auckland are acquired either from Pacific or locally. Similarities mean that disease acquired locally is likely of Pacific origin.